Neuroprotective Properties of Bis-Sulfonamide Derivatives Against 6-OHDA-Induced Parkinson's Model via Sirtuin 1 Activity and in silico Pharmacokinetic Properties - Apiraksattayakul, Setthawut; Pingaew, Ratchanok; Prachayasittikul, Veda; Ruankham, Waralee; Jongwachirachai, Papitcha; Songtawee, Napat; Suwanjang, Wilasinee; Tantimongcolwat, Tanawut; Prachayasittikul, Supaluk; Prachayasittikul, Virapong; Phopin, Kamonrat (Frontiers in Molecular Neuroscience, 2022)
Parkinson's disease (PD) is considered one of highly concerned public health problems in global aging society. Due to the limitations of the currently available drugs on preventing the destructive consequences from disease progression, the discovery of novel neuroprotective agents has gained continual interest. Sulfonamide is an attractive scaffold presented in many drugs and its derivatives were reported for several biological activities. Herein, a series of 17 bis-sulfonamide derivatives were initially tested for their neuroprotective potential and cytotoxicity against the 6-hydroxydopamine (6OHDA)-induced neuronal death in SH-SY5Y cell lines. Subsequently, six neuroprotective compounds (2, 4, 11, 14, 15, and 17) were selected for further investigations on underlying mechanisms. Findings demonstrated that the pretreatment of these selected compounds (5 µM) can significantly restore the level of cell viability, protect against mitochondrial membrane dysfunction, decrease activity of lactate dehydrogenase (LDH), decrease the intracellular oxidative stress as well as enhance the activity of NAD-dependent deacetylase sirtuin-1 (SIRT-1). Molecular docking was performed to reveal binding modes against the SIRT-1 target protein and key interacting residues to support the in vitro findings that these compounds could, in part, act as SIRT-1 activators to exhibit their neuroprotective effect. In silico pharmacokinetic and toxicity prediction was also conducted for guiding the potential successful development. In summary, the six neuroprotective bis-sulfonamides were highlighted as potential SIRT-1 activators to be further developed for PD management.